PREVALENCE AND RISK FACTORS ASSOCIATED WITH OVERWEIGHT AND OBESITY AMONG UNDER THAN 5 YEARS CHILDREN (Iraqi Journal of Medical Sciences, 2016)
Background:Childhood obesity is a serious public health problem with increasing prevalence worldwide.Objectives:To estimate the prevalence of obesity and overweight among under 5 years children and to clarify some factors associated with them like socioeconomic status, sedentary behavior, eating habits etc.Methods: A total of 606 children from those visiting health care center for vaccination or routine care aged 2 months up to < 5 years. The parent (or caretaker) of each child was interviewed using a special questionnaire form provides information about sociodemographic characteristics, inclusion and exclusion criteria, delivery and pregnancy, feeding and nutrition, physical activity, and measurement of weight and height.Results:The prevalence of overweight was 16.8%; of those at risk of obesity were 18.15 %. No significant association found between obesity, age, gender of the children, occupation of the parents, type and size of the family, obstetrical characteristics, eating habits. A significant association between obesity and residency of the children, educational level of parents, added food given to the child and age started to give this food, and physical activity. Conclusion:The study shows that the prevalence of overweight and those at risk of obesity are increased in Iraq in the last decade.Keywords:Overweight, obesity, under 5 years’ children, BMI.
Keywords: Overweight; obesity; under 5 years children; BMI